A Study on Seasonal Variation of Bell’s Palsy in a District Area of Bangladesh (Medicine Today, 2021)
Introduction: Bell’s palsy is a common cranial neuropathy causing acute onset of unilateral lower motor neuron type of seventh cranial nerve palsy that result in ipsilateral facial muscle weakness. The aim of this study was to determine the possible correlation of Bell’s palsy and seasonal influence in a district area of Bangladesh.Materials & Methods: This is an observational study in which we collect, compiled and analyzed the patients information who attended in outpatient department of neuromedicine unit at Cumilla medical college hospital Cumilla from January 2018 to December 2019.Results: In our study, out of 214 patients male were 117(54.7%) and female were 97(45.3%). Age range from 4 to 90 yrs, median age was 40.0±17.6 Number of patients with Bell’s palsy presented in various seasons include 44% during winter, 35% during summer, 9% during fall monsoon and 12% during autumn period. We analyzed the data by using Mean±SD and chi-square test. A significant association was evident in winter and summer season (P=0.04 and P=0.045) respectively.Conclusion: In our present study we found significant relation between seasonal variation and occurrence of Bell’s palsy.Medicine Today 2021 Vol.33(2): 129-132